The Role of Leaders in Managing the Coretax Application Information System Gap - Martinus Sony Erstiawan (Universitas Katolik Darma Cendika, 2025)
This study aims to analyze the information gap in the implementation of the Coretax system, a strategic project of the Indonesian government for tax modernization. Although Coretax was designed to improve efficiency and accountability, there is a discrepancy between positive claims from the bureaucracy and ongoing complaints from taxpayers. This gap indicates a dysfunction in the internal reporting system exacerbated by a